Frequency Migration Challenges and Strategic Decisions-Making in Broadband Wireless Access Networks - Sulaeman, Maman; Wasesa, Meditya (Jurnal Bisnis dan Pemasaran Digital, 2023)
Purpose: The impetus for this study lies in the pressing need for telecommunication companies to adapt to the rapidly evolving technological landscape and regulatory environment to maintain competitiveness and meet increasing consumer demands. Method: This study conducted a comprehensive analysis using SWOT analysis, Qualitative Data Analysis, and the Analytical Hierarchy Process (AHP) to determine the best course of action. Results: This study navigates through the initial stages of identifying the strategic, operational, and financial implications of PT. XYZ Frequency Migration. It delves into the background of Broadband Wireless Access (BWA) technology, the significance of the 3.3 GHz and 10 GHz bands in telecommunications, and the broader context of industry trends necessitating this shift. Methodologically, this research integrates SWOT, stakeholder, qualitative data analysis (QDA), and the Analytical Hierarchy Process (AHP) to provide a holistic understanding of the complexities of migration. Conclusions: The migration of PT. XYZ from the 3.3 GHz to the 10 GHz band represents a strategic move to enhance broadband capacity, service quality, and market competitiveness. Through a holistic evaluation using SWOT, stakeholder input, qualitative data, and the Analytical Hierarchy Process (AHP), the initiative is shown to be both viable and forward-looking despite its complexity. Success hinges on PT. XYZ's ability to synchronize technological upgrades with regulatory compliance, financial prudence, and stakeholder engagement. Limitations: This study is limited by its reliance on qualitative assessments and structured decision-making tools that may not fully capture dynamic market or regulatory shifts. Additionally, the scope did not include real-time performance data post-migration, which could further validate the strategic assumptions. Contributions: This study contributes to the academic and practical understanding of network migration within the telecommunications sector, offering nuanced insights into the complexities of transitioning to higher frequency bands.